Ethics in Government:Axiomatization the Ethics in Governmental Organizations - Seyed Mohammad Moghimi; Rahman Ghaffari (پژوهش‌های مدیریت عمومی, 2016)
In the area of modern business, research in field ethics and professional ethics in public sector organizations, private sector companies and civil society organizations is increasing. The purpose of this research essay on ethics in government agencies in line with the basic requirements to implement and ethical management be provided. The statistical community Grouping stipulated in the Law on Civil Service Management, Ministry of the four groups of four sociocultural, servicing, infrastructure and economic matters. The research method was combined method for collecting data from questionnaires (Alpha 91%) and semi-structured interviews were used. The results demonstrate ethics in government agencies that included orienting rationality, responsibility, equality, cooperation and other ethical issue. The process model of ethical management in government agencies is designed in three dimensions: structural, contextual and behavioral implemented.